Predicting visitor satisfaction in parks: Comparing the value of personal benefit attainment and service levels in Kakadu National Park, Australia - Crilley, G.; Weber, D.; Taplin, Ross (Routledge Taylor & Francis Group, 2012)
Protected area managers are often interested in visitor satisfaction, a complex, multi-dimensional concept. This study of visitors to Kakadu National Park in Australia compares 2 approaches to predicting overall satisfaction and the intention to recommend the park. The first approach involves analyzing importance-performance measures on a range of visitor service quality items. The second approach involves measuring the desire and attainment of perceived benefits associated with a recreation experience. Results show that benefits attained by visitors are stronger predictors of an overall positive response to a park visit than visitor service quality ratings. Two types of benefits emerge from factor analysis—benefits derived from nature and benefits derived from relaxation—and these factors show varying degrees of correlation with overall response to the park depending on proximity of the respondents’ home to the park. The results suggest greater attention should be paid to the benefits people desire from their visits and increases our understanding of what benefits are dependent on the environment (biophysical, social, and managerial), the activity visitors participate in, or a combination of both. Such information can help park staff to create experiences likely to facilitate attainment of benefits that are important to visitors.